Foot Notes: a podcast about walkability and race - Linke, Lily. (Tufts University. Tisch Library., 2021)
Thesis (M.A.)--Tufts University, 2021.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Julian Agyeman.; Committee: Penn Loh.; Keywords: Urban planning, Sociology, and Transportation.; The prevailing approach to researching, designing, and implementing walkability focuses almost exclusively on the built environment. This approach operates under the assumption that "good design" is objective, neutral, and universal. This is simply not true. Walking is deeply personal, political, social, and cultural. Our experience of walking through public space is determined just as much by the identities we inhabit as by the space itself. This original podcast series utilizes a sociocultural approach to examine the intersection of walkability and race, and specifically the experiences of Black pedestrians in the United States.